Generalist CEOs and the Cost of Debt: Evidence from Indonesia - Suhardianto, Novrys; Ningsih, Sri; Rahmatulloh, Sahrian Aditya; Nasih, Mohammad; Putri, Oudyza Oktavia; Nuryaddin, Zayyan Ahmad (Gadjah Mada International Journal of Business, 2026)
This study examines the impact of generalist CEOs on the cost of debt in Indonesia, using data from public companies listed on the Indonesia Stock Exchange (IDX) between 2015 and 2021. Employing panel data regression with a random effects model, Coarsened Exact Matching (CEM), and Heckman's two-stage regression, the results indicate that companies with generalist CEOs incur higher debt costs. Additional analyses confirm that specialist CEOs are associated with lower debt costs, reinforcing the main findings. These results highlight how generalist CEOs, with their broad industry experience, may increase perceived financial risk, leading creditors to impose higher interest rates. From a practical perspective, these findings provide valuable insights for investors, corporate boards, and policymakers in aligning CEO selection processes with firm-specific financial objectives to mitigate risks. From a social perspective, the findings underscore the importance of addressing financial risks associated with generalist CEOs, particularly in Indonesia, where high information asymmetry and inefficient capital markets persist. Elevated borrowing costs could hinder corporate investments and broader economic growth. By integrating these findings into governance practices, this study contributes to sustainable development and financial stability in emerging markets